2017
DOI: 10.1039/c7cp01286a
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic neutron scattering study of reline: shedding light on the hydrogen bonding network of deep eutectic solvents

Abstract: The solids choline chloride and urea, mixed in a 1 : 2 molar proportion, form the iconic deep eutectic solvent "Reline". A combination of computational and vibrational spectroscopy tools, including inelastic neutron scattering (INS), have been used to probe intermolecular interactions in the eutectic mixture. Reline's experimental spectra were estimated using discrete and periodic ab initio calculations of a molecular aggregate with two choline chloride and four urea units. This is the minimum size required to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 146 publications
(166 citation statements)
references
References 62 publications
6
160
0
Order By: Relevance
“…The calculated INS spectrum of PMACC (Figure 4, middle) provided a good qualitative description of the experimental spectrum (Figure 4, top). It should be mentioned that the INS spectrum of PMACC was mostly dominated by the vibrations of the choline chloride fragment, and presented a remarkable similarity with the INS spectrum of "reline" (choline chloride and urea eutectic mixture) [46] shown in Figure 4 (bottom). This similarity provided further reliance on the interpretation of spectral features, as discussed below.…”
Section: Ins Spectrum Of Pure Compoundssupporting
confidence: 52%
See 1 more Smart Citation
“…The calculated INS spectrum of PMACC (Figure 4, middle) provided a good qualitative description of the experimental spectrum (Figure 4, top). It should be mentioned that the INS spectrum of PMACC was mostly dominated by the vibrations of the choline chloride fragment, and presented a remarkable similarity with the INS spectrum of "reline" (choline chloride and urea eutectic mixture) [46] shown in Figure 4 (bottom). This similarity provided further reliance on the interpretation of spectral features, as discussed below.…”
Section: Ins Spectrum Of Pure Compoundssupporting
confidence: 52%
“…In addition, it displays intensity changes coinciding with several bands of both BC and The well-defined bands emerging in the 200-350 cm −1 region can be reasonably assigned to the torsional motions of the methyl groups of methacroylcholine moieties. In a previous INS report [46], it was observed that methyl torsions of choline chloride are good probes of the proximity of chloride ions relative to the methyl groups. In the crystal, chloride ions are hydrogen-bonded to the methyl groups and the methyl torsional motions are observed as sharp bands in the 286-349 cm −1 interval.…”
Section: Interactions Between Components In the Nanocompositesmentioning
confidence: 97%
“…in 2004, are composed of at least a hydrogen bond acceptor (HBA) and a hydrogen bond donor (HBD) species, which, when mixed, establish strong hydrogen‐bonding interactions and form eutectic mixtures with a melting point lower than the starting compounds alone, often becoming liquid at conditions close to room temperature . The eutectic mixture composed of choline chloride and urea has attracted significant attention as a reference DES owing to its unique properties . The properties of DESs, along with their straightforward preparation, make them an ideal medium for a variety of applications, such as catalysis, organic synthesis, electrochemistry, materials chemistry, and extraction processes, including biomass fractionation and processing …”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] The eutectic mixture composed of choline chloride and urea has attracted significant attention as ar eference DES owing to its unique properties. [9] The properties of DESs, along with their straightforward preparation, make them an ideal mediumf or av ariety of applications, such as catalysis, organic synthesis, electrochemistry,m aterials chemistry,a nd extractionp rocesses, [5,8,10,11] including biomass fractionation and processing. [7] Their potential as green solvents has attracted growing interest owing to their resemblance to ionic liquids( ILs), [12] which are known for their potentiali nb iomass pretreatment and fractionation.…”
Section: Introductionmentioning
confidence: 99%
“…One of the modelsi st he complex 3D network formed by anions and hydrogen in molecular compounds. [8,15] TGA curves show that 18C6 is less thermostable than KTFB (Figures S5 and S6). In addition, DES with low crown ether content is more thermally stable than that of high content.…”
mentioning
confidence: 99%